Mode of action of Saccharomyces cerevisiae in enteric methane mitigation in pigs. (24th July 2017) - Gong, Y. L.; Liang, J. B.; Jahromi, M. F.; Wu, Y. B.; Wright, A. G.; Liao, X. D.
Abstract : The objectives of this study were to determine the effect and mode of action of Saccharomyces cerevisiae (YST2) on enteric methane (CH4 ) mitigation in pigs. A total of 12 Duroc×Landrace×Yorkshire male finisher pigs (60±1 kg), housed individually in open-circuit respiration chambers, were randomly assigned to two dietary groups: a basal diet (control); and a basal diet supplemented with 3 g/YST2 (1.8×10 10 live cells/g) per kg diet. At the end of 32-day experiment, pigs were sacrificed and redox potential (Eh), pH, volatile fatty acid concentration, densities of methanogens and acetogens, and expression of methyl coenzyme-M reductase subunit A gene were determined in digesta contents from the cecum, colon and rectum. Results showed that S. cerevisiae YST2 decreased ( P <0.05) the average daily enteric CH4 production by 25.3%, lowered the pH value from 6.99 to 6.69 in the rectum, and increased the Eh value in cecum and colon by up to −55 mV ( P <0.05). Fermentation patterns were also altered by supplementation of YST2 as reflected by the lower acetate, and higher propionate molar proportion in the cecum and colon ( P <0.05), resulting in lower acetate : propionate ratio ( P <0.05). Moreover, there was a 61% decrease in Methanobrevibacter species in the upper colon ( P <0.05) and a 19% increase in the acetogen community in the cecum ( P <0.05) of treated pigs. Results of our study concluded that supplementation of S. cerevisiae YST2 at 3 g/kg substantially decreased enteric CH4 production in pigs.